Ustavne omejitve in prepovedi zakonodajnega referenduma - Kaučič, Igor (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2014)
With the amendment of article 90 of the Constitution of the Republic of Slovenia, following the model of comparable European states, Slovenia too introduced restrictions and prohibitions on the legislative referendum. A legislative referendum can no longer be called for laws pertaining to emergency measures to ensure the defence of the state, security, or the elimination of the consequences of natural disasters; financial and budgetary laws as well as the law adopted for the implementation of the state budget; laws ratifying international treaties; and laws eliminating unconstitutionality in the field of human rights and fundamental freedoms or any other unconstitutionality. Delaying the adoption of such laws, and their rejection in a referendum in particular, would represent a serious hindrance for the functioning of the state and the execution of its fundamental functions - especially in adopting urgent legislative measures. Restrictions and prohibitions of referendum decision-making are characteristic of those systems where the referendum may be demanded by the voters. In systems where the referendum is in the hands of the parliamentary majority, the need for express prohibitions is considerably smaller, if not redundant, since the parliament independently decides on the appropriateness of a referendum decision-making on such laws.
Keywords: democracy; demokracija; referendum; pravna ureditev; ustave; človekove pravice; human rights